DEVELOPMENT OF STANDARD OPERATING PROCEDURES FOR OPERATING REFRIGERATION MACHINERY ON FISHING VESSELS - Abrori, Muhammad Zaki Latif; Demeianto, Bobby; Tumpu, Mula; Sandri, Muhammad (Politeknik Kelautan dan Perikanan Dumai, 2024)
Refrigeration machines in fishery companies are widely used to maintain the quality of seafood products to keep them fresh. These machines are quite complex, so operating them correctly is crucial, as fatal operational errors can lead to the damage of the refrigeration equipment. The absence of written SOPs has the potential for non-standardized operations. Therefore, this article aims to develop Standard Operating Procedures (SOPs) for operating refrigeration machines on fishing vessels. To achieve this goal, data from the refrigeration system is used, and competent machine crew members are involved to obtain valid data. The data obtained is analyzed using a quantitative descriptive method. A proposed design of Standard Operating Procedure (SOP) with a cross-functional flow chart diagram has been produced as a guideline for operating refrigeration machines on fishing vessels. Based on the analysis, this SOP Draft has met the eligibility criteria for use. The SOP this machinery are highly significant in assisting the machine crew in ensuring that the machines are operated in a controlled manner following the correct procedures.